PELATIHAN GURU SD BERBASIS NILAI KEBERAGAMAN UNTUK PENGUATAN PEMBELAJARAN PENDIDIKAN PANCASILA - Maretha Dellarosa; Vicky Dwi Wicaksono; Hendrik Pandu Paksi; Ari Metalin Ika Puspita; Caesaria Primananda Wiedy; Cindy Cynthia Devi (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2026)
Intolerance is a social issue that poses a major challenge in many countries, especially multicultural ones. Many factors contribute, particularly the lack of relevant examples of practices by society regarding diversity and an education system that does not accommodate discussions about differences. Therefore, educational institutions play a crucial role in creating a harmonious social environment. Training programs to appreciate the value of diversity, particularly in Pancasila Education, are crucial because they impact the development of national character. To achieve this goal, teachers play a key role in preparing students to interact in social environments. Teachers are expected to contribute to building a harmonious social environment that fosters mutual respect for differences. The training, held in Pacitan Regency, East Java, attracted 13 participants. It consisted of three stages: preparation, implementation, and evaluation. The training methods used were lectures, discussions, and questions and answers. The training results showed that participants had a relevant understanding of diversity. Furthermore, they successfully designed programs related to diversity appreciation that can be implemented in their respective classrooms.